Trainingspläne - Workouts
At this site one can find the links to the workouts of our first training group. With the publication of these workouts we would like to go a new path and would like to stimulate the exchange of workouts with other swimming clubs. The workouts are designed for the first training group of the GSV. Training times are regularly four times a week, once in a 25m pool. Following you will find the workouts for the 50m pool. The group consits of kinds and youths in the age of 13 to 21. Best swimmer presently is Kerstin Thiel (84), who managed with some of those workouts a time of 1.08,7 on 100m backstroke. Training is from 18:00 to 19:45. Special strength training is not offered, mostly becauuse of a lack of time of the head coach. Training with bands and the own weight is done regularly. The swimmerrs are mostly sprinters and middle distance swimmers. For long distance swimmers we are not able to offer the necessary volume. Mainly we practice four macrocycles: 5 -7 weeks endurance 4 - 6 weeks special endurance 4 weeks pre-competition phase with regular competions 2- 3 weeks taper, with 2 weeks recovery afterwards Seasons highs are regional championships end of November, German team competitions in Jan/Feb and again national and regional championships in May/June. The workouts should be selfexplaining.